Developing best practice guidelines for lake modelling to inform quantitative microbial risk assessment. (April 2022) - Yu, Songyan; Sturm, Katrin; Gibbes, Badin; Kennard, Mark J.; Veal, Cameron J.; Middleton, Duncan; Fisher, Paul L.; Rotherham, Simon; Hamilton, David P.
Abstract: Numerical models of lakes and reservoirs have been widely applied to provide quantitative forecasts of pathogen occurrence and persistence in source water to inform quantitative microbial risk assessment (QMRA). There is an emerging need in the water supply industry for a set of best practice modelling guidelines, supporting consistent and repeatable use of lake modelling approaches that could be used to provide quality assurance to water authorities and regulators. To aid in the development of these guidelines, we conducted a literature review to summarise common modelling steps from existing water modelling guidelines as the basis for best practice guidelines for lake modelling. We also report on the results of a workshop, expert interviews, and online surveys that identify common challenges and requirements for each step. The summarised lake modelling steps and key requirements pave the way to complete the development of best practice guidelines for lake modelling to inform QMRA. Highlights: Lake modelling complements pathogen monitoring for microbial risk assessment. Survey participants regard best practice guidelines for lake modelling as useful. Best practice guidelines for lake modelling consist of six common modelling steps. Supporting activities for each modelling step are proposed. Future studies are needed to specify best practice guidance for the requirements.